Transoral Robotic Surgery and the Unknown Primary: A Highly Effective Technique for Identifying the Tumor. (23rd August 2013) - Byrd, James K.; Albergotti, William G.; Davis, Kara; Kim, Seungwon; Ferris, Robert L.; Johnson, Jonas T.; Duvvuri, Umamaheswar
Abstract : Objectives: 1) Describe the use of transoral robotic surgery (TORS) in the management of patients with unknown primary carcinoma of the head and neck. 2) Report the efficacy of TORS for patients with unknown primaries in our updated series, the largest reported series of such patients. Methods: A retrospective chart review was performed on patients with new occult primary squamous cell carcinoma of the head and neck with non‐diagnostic imaging and/or endoscopy who were treated with TORS at a tertiary hospital between 2009 and 2012. Tumor identification rate and characteristics were analyzed. Results: 206 head and neck robotic cases were performed at our institution between December 2009 and December 2012. Three surgeons performed TORS on 22 patients for occult primary squamous cell carcinoma. Of these, 11 had bilateral base of tongue resection, 3 had unilateral base of tongue resection, and the remainder had a combination of base of tongue procedures and tonsillectomy. The primary tumor was located in 19/22 (86.4%) patients. Mean tumor size was 1.03 cm +/‐ 0.66 cm and 9/22 (40.9%) patients had negative resection margins after the primary procedure. Conclusions: TORS is an effective procedure to locate the primary tumor in patients with cervical lymph node metastases and no obvious source. Bilateral base of tongue resection should be considered as part of the exam under anesthesia for these patients, particularly if the palatine tonsils have already been removed.